Hentei-Dauria fold system of the Mongolia-Okhotsk belt: magmatism, sedimentogenesis, and geodynamics - I. V. Gordienko; O. R. Minina; L. I. Vetluzhskikh; A. Ya. Medvedev; D. Odgerel (Геодинамика и тектонофизика, 2018)
The geostructural, petrological, geochemical, geochronological and biostratigraphic studies were conducted in the Hentei-Dauria fold system of the Mongolia-Okhotsk orogenic belt. This Paleozoic system is composed mainly of three heterochronous rock associations related to the onset and development of oceanic basins and active margins in the conjugation zone of the Siberian continent and the Mongolia-Okhotsk ocean. This region developed in three stages: (1) Late Caledonian (Ordovician – Early Silurian), (2) Early Hercynian (Late Silurian – Devonian), and (3) Late Hercynian (Carboniferous–Permian). In the Late Caledonian, oceanic seafloor spreading was initiated, deep-sea siliceous deposits were formed, basaltic and andesitic pillow lavas were erupted, and layered and cumulative gabbros, gabbro-dolerite dykes and subduction zones with island-arc magmatism were formed. After a short quiescence period, new zones of spreading and subduction occurred at the active margins of the Mongolia-Okhotsk ocean in the Early Hercynian. In the Late Hercynian, large back-arc sedimentary basins, accretionary prisms and connecting intraplate magmatic complexes were formed in all structures of the Hentei-Dauria fold system. As a result of our studies, we propose a comprehensive model showing the geodynamic development of the Hentei-Dauria fold system that occurred in the area of the Mongolia-Okhotsk Ocean and its margins.